Strategic management proposal to overcome economic efficiency in the positioning of banking products (Original) (REDEL. Revista Granmense de Desarrollo Local, 2019)
Several personalities (Castro Ruz, F; Castro Ruz, R,) have talked about the need for banking institutions to be effective in their management and with positive economic results, which in addition to being a goal for any state economic organization, is clearly established and assumed in the guidelines of the economic and social policy of the Party and the Revolution. It has been studied a lot how to introduce and bring to the branches a clear concept of competition, of active commercial activity based on the interests of the institution, of the implementation of the marketing policy, of improvement of the quality of the services, among others Management trends Using the acquired techniques and knowledge, a critical characterization and analysis of the object studied was carried out based on aspects of the financial economic position as a tool for banking management during the 2016-2017 period; The main problem was identified and innovations were proposed to improve service quality and strengthen control and results in branch management. The proposals were made after reviewing different management models such as human resources, quality, maintenance, innovation and environment, these have allowed the current diagnosis of the branch, identify threats, opportunities and plan strategies in the short, medium and long term to overcome the barrier and maintain a continuous increase in results.
Keywords: strategic; positioning; economic; marketing; financial